Independent evolution of allometric traits: a test of the allometric constraint hypothesis in island vines. (15th November 2018) - Biddick, Matthew; Hutton, Ian; Burns, K C
Abstract: The capacity of traits to evolve independently of one another is thought to be constrained by their allometry (i.e. the allometric constraint hypothesis). Here, we tested the allometric constraint hypothesis using changes in leaf–stem morphology of nine vine species inhabiting islands in the south-west Pacific. We first quantified leaf–stem allometry and tested whether it differs between islands and the mainland. We then quantified changes in leaf and stem size on islands and tested whether they were correlated. Leaf–stem allometry varied among species but did not differ between islands and the mainland. Leaf gigantism characterized island populations, whereas changes in stem size scaled with latitude. Contrary to predictions of the allometric constraint hypothesis, changes in leaf size were not associated with a concomitant change in stem size. Overall, the results suggest that trait allometry does not prohibit independent trait evolution.